IDENTIFICATION AND CHARACTERISATION OF COI GENE IN FEMALE SUMATRAN ELEPHANT (Elephas maximus sumatranus) IN ELEPHANT TRAINING CENTRE, WAY KAMBAS NATIONAL PARK - Virnarenata, Elsa; Rustiati, Elly Lestari; Priyambodo, Priyambodo; Srihanto, Eko Agus; Pratiwi, Dian Neli (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2021)
Sumatran elephant is a subspecies of endemic Asian elephants on the island of Sumatra and is included in the Red List of the International Union for Conservation of Nature (IUCN) with critically endangered status. The building of the Elephant Training Centre (ETC) in Way Kambas National Park (WKNP) is one of the conservation efforts of Sumatran elephants. Small and closed population size lead to an increased risk of inbreeding that triggers reduction in genetic variation and viability and increases the risk of extinction. The phylogenetic pattern of Sumatran elephants in Indonesia has shown a low population genetic diversity. Genetic diversity information is indispensable to support the direction of decision making in Sumatran elephant conservation policy. The DNA isolation of Sumatran elephants in ETC, WKNP has performed as a first step to trace its genetic variation. The advanced step of DNA isolation is the use of cytochrome oxidase subunit I (COI) gene for identification of genetic characteristics in Sumatran elephants. The COI gene is one of the genes on the mitochondrial genome and in molecular studies it is used as a genetic marker to study genetic characteristics between species and individuals. Identification and characterisation are done by sequencing process and data analysis in the form of electroforegram using Molecular Evolution Genetics Analysis (MEGA) software version 6.0. to see the genetic diversity of the female Sumatran elephant population in ETC, WKNP. Based on the results of the analysis it is indicated that the genetic distance of 24 individual female Sumatran elephant from PLG, TNWK is 0.000 with a homology value of 100%, strengthened by the construction of phylogenetic tree. The absence of genetic distance indicates a close genetic relationship, so it can be concluded all individual female Sumatran elephants in the PLG, TNWK is derived from one population group.